Evaluasi Keberhasilan Sistem Informasi Absensi dan Penggajian Terintegrasi Berdasarkan Model DeLone dan McLean - Imam Tauzy; Sri Dianing Asri (JSAI (Journal Scientific and Applied Informatics), 2026)
Employee attendance and payroll systems play a crucial role in human resource management as they directly affect payroll accuracy, transparency, and employee satisfaction. However, many previous studies have primarily focused on system development and functional testing, with limited attention to comprehensive system success evaluation. This gap highlights the need for an evaluative approach that measures system quality, information quality, and the benefits perceived by users. This study aims to evaluate the success of an integrated web-based attendance and payroll information system using the DeLone and McLean Information System Success Model. The research employed a quantitative approach with a survey method, using a Likert-scale questionnaire distributed to system users. Data were analyzed using descriptive quantitative analysis and converted into percentage values. The results indicate that the system achieved a success rate of 92%, categorized as very good. These findings demonstrate that the system has high system quality and information quality and provides significant net benefits in improving administrative efficiency and payroll information transparency for employees.